En-garde: Source Evaluations in the Digital Age - Denton, Courtney A.; Muis, Krista R.; Dubé, Adam K.; Armstrong, Skylar (Advances in Social Sciences Research Journal, 2022)
Students have difficulty assessing the quality of information. They often rely on content-focused criteria to make reliability assessments and, as a result, may accept inaccurate information. Despite the impact of poor source evaluation skills, educational researchers have not widely examined source evaluation behaviours in authentic environments or tasks. Students’ epistemic cognition, or their thinking about the epistemic properties of specific knowledge claims and sources, is one promising avenue to better understand their source evaluation behaviours. Two studies were conducted to explore students’ epistemic thinking. In Study 1, college students (n = 12) reported their reliability criteria in focus group interviews. Four of these participants (n = 4) also examined the reliability of an online news article. Grounded theory was used to infer students’ epistemic ideals and reliable epistemic processes. In Study 2, students (n = 43) rank-ordered two news articles and justified how they assigned each article’s rank in a written response. Most students were able to accurately rank-order the articles using relevant epistemic processes. Cluster analysis was used to characterize the evaluation criteria used. Surprisingly, more participants who justified their decisions using relevance criteria accurately rank-ordered the articles. The role of direct and indirect indicators of reliability are discussed through the lens of the Apt-AIR framework of epistemic thinking.